1994
DOI: 10.1246/cl.1994.1451
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation of Isobutane with Butenes Catalyzed by a Cesium Hydrogen Salt of 12-Tungstophosphoric Acid

Abstract: A solid superacid, Cs2.5H0.5PW12O40, catalyzed the alkylation of isobutane with butenes at room temperature. Cs2.5H0.5PW12O40 was much more active than SO42−/ZrO2, a well-known solid superacid, and was highly selective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…9,10. An aqueous solution of Cs 2 CO 3 was added dropwise to that of H 3 PW 12 O 40 , and the obtained precipitate was evaporated at 318 K followed by aging overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10. An aqueous solution of Cs 2 CO 3 was added dropwise to that of H 3 PW 12 O 40 , and the obtained precipitate was evaporated at 318 K followed by aging overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Various catalyzed reactions such as alkylation, ester decomposition, acylation, Diels-Alder reaction, have been reported to proceed on Cs 2.5 H 0.5 PW 12 O 40 . [9][10][11] Recently, Limoges et al 12 reported the heterployacides can be used as the catalyst of the anode and cathode in PEMFCs.…”
mentioning
confidence: 99%
“…Owing to their strong acidities, heteropoly acids have been explored as potential catalysts for alkylation of isobutane with butene but the literature on this subject is scarce. 620,621 In these cases, K+, Rb+, Cs+, and NH4+ salts of tungstophosphoric heteropoly acid were preferred as catalysts and they could form tribranched products in good yields at relatively low temperatures (Table 23). Moreover, it appears that they give better results than superacid S042-/Zr02 catalysts.…”
Section: Inorganic Solid Acidsmentioning
confidence: 99%
“…Because of their multifunctionality, heteropolyacids catalyze a wide variety of reactions including hydration and dehydration, condensation, reduction, oxidation, and carbonylation chemistry with Keggin-type anions of V, Mo [168], [169], [171][172][173]. A commercially important process, the oxidation of methacrolein, is catalyzed by a Cs salt of H 4 PVMo 11 O 40 .…”
Section: Vanadium Phosphatesmentioning
confidence: 99%